2008
DOI: 10.1007/s10409-008-0164-z
|View full text |Cite
|
Sign up to set email alerts
|

Computational aerodynamics of low Reynolds number plunging, pitching and flexible wings for MAV applications

Abstract: Micro air vehicles (MAV's) have the potential to revolutionize our sensing and information gathering capabilities in environmental monitoring and homeland security areas. Due to the MAV's' small size, flight regime, and modes of operation, significant scientific advancement will be needed to create this revolutionary capability. Aerodynamics, structural dynamics, and flight dynamics of natural flyers intersects with some of the richest problems in MAV's, including massively unsteady three-dimensional separatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
51
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(52 citation statements)
references
References 37 publications
1
51
0
Order By: Relevance
“…The aerodynamics of flapping wings is a combination of several complex phenomena, including Wagner effects, wake capture, leading edge vortex, near fling, and added mass. Results of recent experimental and theoretical investigations of flapping flight have been covered in reviews underlying fluid mechanics and aerodynamics [1][2][3], flapping flight controls [4], and theoretical and numerical modeling of unsteady flowfields in the near and far wakes of oscillating wings [5,6].…”
mentioning
confidence: 99%
“…The aerodynamics of flapping wings is a combination of several complex phenomena, including Wagner effects, wake capture, leading edge vortex, near fling, and added mass. Results of recent experimental and theoretical investigations of flapping flight have been covered in reviews underlying fluid mechanics and aerodynamics [1][2][3], flapping flight controls [4], and theoretical and numerical modeling of unsteady flowfields in the near and far wakes of oscillating wings [5,6].…”
mentioning
confidence: 99%
“…The time history and power spectrum of the lift on a flat plate undergoing the same trigonometric motion are plotted in Figures 3(a) and 3(b), respectively. These oscillations of the same frequency for x-translation and rotation are considered to mimic the motion of insects and birds' wings, 3,13 i.e., ω x = ω θ . From Figure 3(b), we observe that the lift spectrum exhibits a peak at twice the frequency of flapping motion as well as smaller peaks at the first and third harmonics of that frequency.…”
Section: Resultsmentioning
confidence: 99%
“…(1) and (2). At every time step, the governing equation for the discrete stream function is then discretized and solved numerically.…”
Section: Immersed-boundary Flow Solvermentioning
confidence: 99%
“…Although (passive) flexibility of wing/fin has long been recognized as an important factor in the aerodynamic (hydrodynamic) performance of insect flight or fish swimming, it has received little attention until recently (see [1,2] for a comprehensive review). By using a combination of computational and analytic methods, Daniel and Combes [3] have shown that the deformation in flapping wings was dominated less by aerodynamic loading than by inertial and elastic forces.…”
Section: Introductionmentioning
confidence: 99%